Palatability and Durability Test of Coumatetralyl Rodenticide with Various Flavors and Baits to Malayan Field Rats (Rattus tiomanicus Mill.) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Rats are wild animals that are often found in various habitats and become a nuisance in human life. Rats can cause damage and losses to crops, one of which is oil palm plantation. Therefore, control efforts are needed, one of which is chemical control using rodenticides. This study aimed to determine the level of attractiveness of Malayan field rats to various formulations of coumatetralyl-based rodenticides with cereal-based baits and with vegetable and animal flavorings. Study also conducted to measure the durability and effectiveness of these rodenticides after being exposed in the oil palm crop. The types of rodenticides used were coumatetralyl rodenticides in rice bait and rice plus wheat baits, with chocolate, pandanus, strawberry, and mealworm flavorings. This study consisted of three tests: Palatability, durability, and mealworm tests, each method lasts for three days pre-test, three days test, and fourteen days post-test. The methods used were choice test with eight treatments each for palatability and durability, and two treatments for mealworm test. Data were analyzed using a randomized block design, R Studio with Tukey's test at α = 5%. The results showed that the consumption of Malayan field rats on coumatetralyl rodenticides with flavored baits in the palatability and durability tests was not significantly different, while it was significantly different in the mealworm test. Coumatetralyl rodenticides with pandanus and chocolate flavors, with rice and rice-wheat baits, and positive control rodenticides with mealworms were more preferred by Malayan field rats than others. Further research is aimed at testing the coumatetralyl rodenticide with the best type of bait and flavoring agent for application in oil palm plantations to kill pest rats and reduce the damage they cause to oil palm fruit.